On the problem of identification for eggs of alaska place Pleuronectes quadrituberculatus (Pleuronectidae) from ichthyoplankton collections in the northern Okhotsk Sea - R. R. Yusupov; Rus. R. Yusupov (Известия ТИНРО, 2022)
Species composition in catches of the ichthyoplankton survey conducted on June 4, 2021 in the periphery of the Tauiskaya Guba Bay (northern Okhotsk Sea) is considered. Eggs of 3 fish species were collected, the portion of alaska place was 1.3 %. Specific pigmentation of the alaska place embryos was defined that allowed to identify reliably the eggs of this species, in combination with other signs.